2020
DOI: 10.21608/ejnf.2020.95807
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Date Palm Leaves Treated With Enzymes in Small Ruminants Feeding

Abstract: im of the current study was to investigate the effects of feeding small ruminants on diets contained date palm tree leaves (DPL) incubated or not with enzymes. Biological treatments were used in laboratory experiment to determine the effect of using different enzymes (Cellulase, Taninnase, Fibrolytic and combinations of each with other) on chemical composition of date palm leaves. In vitro trail was conducted using diets contained 40% DPL incubated with enzymes to study in vitro nutrients disappearance. A dige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
(36 reference statements)
2
6
0
Order By: Relevance
“…Kholif and Aziz (2014) found that addition of cellulytic enzymes to goat diets significantly (P<0.01) increased ruminal ciliate protozoa counts. Aziz (2020) found that feeding sheep on diets contained DPL treated with cellulase or fibrolytic enzymes or a combination of them increased number of ruminal protozoa compared with that fed untreated.…”
Section: Ruminal Ciliate Protozoamentioning
confidence: 97%
See 1 more Smart Citation
“…Kholif and Aziz (2014) found that addition of cellulytic enzymes to goat diets significantly (P<0.01) increased ruminal ciliate protozoa counts. Aziz (2020) found that feeding sheep on diets contained DPL treated with cellulase or fibrolytic enzymes or a combination of them increased number of ruminal protozoa compared with that fed untreated.…”
Section: Ruminal Ciliate Protozoamentioning
confidence: 97%
“…Also, Khorshed (2000) Bassuny et al (2003) and 2009indicated that creatinine concentration in serum of sheep fed biologically treated roughage was higher (P<0.01) than values of those fed controls, and the values ranged from 1.06 to 1.25 (mg/dl) for creatinine. Moreover, Aziz (2020) stated an improvement in blood serum total protein, Albumin, Globulin, urea, AST and ALT for sheep fed DPL treated with cellulase or fibrolytic enzymes or a combination of them compared with that fed untreated. Digestibility trail: Feed intake:…”
Section: Blood Parametersmentioning
confidence: 99%
“…The present results are in agreement with Aziz (2009) who showed that olive tree leaves ensiled with biological treatments increased DM, OM, EE and CP and decreased CF, NDF, ADF and ADL. Also, Aziz (2019 and2020) reported that ensiling DPL with urea or with fibrolytic enzymes enhanced chemical composition especially OM and CP, while CF, NDF, ADF and ADL were decreased.…”
Section: Chemical Composition and Cell Wall Constituents Of Feedstuffsmentioning
confidence: 99%
“…Abd El Tawab et l. (2018) reported that ammonia concentration recorded higher value for olive cake silage treated with fibrolytic enzymes compared with control. Aziz (2019 and2020) found an improvement in concentrations of ruminal pH, TVFA's, NPN, NH3-N, TN, TP and MP for sheep fed DPL ensiled with urea or with enzymes.…”
Section: Nitrogen Utilizationmentioning
confidence: 99%
See 1 more Smart Citation